ANALYZING POLITICAL DEBATE STRATEGIES: TOULMIN'S ARGUMENTATION MODEL IN THE 2024 BINJAI MAYORAL ELECTION - Pulungan, Hendra; Anshori, Dadang S.; Sumiyadi, Sumiyadi; Mulyati, Yeti (Journal of Pragmatics and Discourse Research, 2025)
Political debates play a crucial role in democratic processes, allowing candidates to present their ideas, defend policies, and persuade voters. This study applies Toulmins argumentation model to analyze the rhetorical strategies used in the 2024 Binjai Mayoral candidate debate. Using a qualitative descriptive approach, data were collected through video recordings, transcripts, and documentation of debate discussions. The analysis identifies the presence and structure of Toulmins six argumentation components: claim, grounds, warrant, backing, modal qualifier, and rebuttal. Findings indicate that while candidates frequently use claims and grounds, they often lack strong warrants and rebuttals, leading to arguments that are persuasive but not necessarily well-justified. Additionally, emotional appeals and rhetorical tactics often replace logical reasoning, impacting the overall quality of the debate. The study highlights the need for stronger argumentation frameworks in political communication, emphasizing the importance of data-driven and evidence-based claims. This research contributes to the field of political communication by providing insights into argumentation trends in modern political debates. The findings suggest that training political candidates in structured argumentation techniques could improve public discourse and enhance voters ability to critically assess political messages. Future research should consider comparative analyses of debates across different political levels and the role of media framing in shaping argumentation effectiveness.